الهيدروجين الأخضر - .خلفاوي, إسراء; .طريلي ,مارية; .عريق, آية (University of Eloued جامعة الوادي, 2025)
تشهد الساحة العالمية تحولات متسارعة نحو مصادر الطاقة النظيفة في ظل التغي ا رت المناخية المتفاقمة والالت ا زمات الدولية بخفض الانبعاثات الكربونية. في هذا الإطار، يبرز الهيدروجين الأخضر كأحد الحلول الواعدة بفضل إمكانية إنتاجه من مصادر متجددة دون انبعاثات ضارة. تهدف هذه الد ا رس ة النظرية إلى تقديم د ا رسة تحليلية شاملة حول منظومة الهيدروجين الأخضر، بدءًا من تقنيات إنتاجه، مرو اً ر بوسائل نقله وتخزينه، وصولًا إلى تطبيقاته في مختلف القطاعات، مع تسليط الضوء على التحديات التي تواجه انتشاره والفرص التي يتيحها. تم الاعتماد على مجموعة من الد ا رسات والم ا رجع الحديثة في هذا المجال. وقد خلصت الد ا رسة إلى أن اعتماد الهيدروجين الأخضر على نطاق واسع لا ي ا زل مشروطًا بتطور التكنولوجيا، وانخفاض التكاليف، وتوفر بنية تحتية مناسبة، بالإضافة إلى الدعم السياسي والتشريعي. كما أظهرت النتائج أن الهيدروجين الأخضر قد يشكل دعامة أساسية لتحقيق انتقال طاقوي مستدام إذا ما توفرت له البيئة المواتية للنمو.The global landscape is undergoing a rapid transition toward clean energy sources, driven by the intensifying climate crisis and international commitments to reducing carbon emissions. Within this context, green hydrogen has emerged as one of the most promising solutions, due to its potential to be produced from renewable sources without generating harmful emissions. This theoretical study aims to provide a comprehensive analytical exploration of the green hydrogen ecosystem, encompassing its production technologies, transportation and storage methods, and applications across various sectors. Particular emphasis is placed on identifying the main challenges hindering its widespread deployment, as well as the potential opportunities it offers for sustainable energy transformation. The study draws upon a wide range of recent academic and technical references in the field. Findings suggest that the large-scale adoption of green hydrogen remains contingent upon technological advancements, cost reductions, the availability of appropriate infrastructure, and strong political and legislative support. Moreover, the results indicate that green hydrogen could serve as a foundational pillar in achieving a sustainable energy transition—provided that the enabling conditions for its development are effectively established
مذكرة تخرج ماسترهندسة كهربائية
Keywords: الطاقة النظيفة، الانبعاثات الكربونية، مصادر متجددة، الهيدروجين الأخضر; Green hydrogene; renewable energy; clean energy; carbon emissions